Angiogenic Potential of 3-Nitro-4-Hydroxy Benzene Arsonic Acid (Roxarsone) - Basu, Partha (National Institute of Environmental Health Sciences, 2008)
BACKGROUND: Roxarsone (3-nitro-4-hydroxy benzene arsonic acid) is an arsenic compound widely used in the poultry industry as a feed additive to prevent coccidiosis, stimulate growth, and to improve tissue pigmentation. Little is known about the potential human health effects from roxarsone released into the environment from chicken waste or from residual compound in chicken products. OBJECTIVE: The growth potentiation and enhanced tissue pigmentation suggest that low levels of roxarsone exposure may have an angiogenic potential similar to that of inorganic arsenite (As(III)). The goal of this investigation was to test the hypothesis described above using cultured human aortic and lung microvascular endothelial cells in high-content imaging tube-forming assays and begin developing a molecular level understanding of the process. METHODS: We used a three-dimensional Matrigel assay for probing angiogenesis in cultured human endothelial cells, and a polymerase chain reaction (PCR) array to probe the gene changes as a function of roxarsone or As(III) treatment. In addition, we used Western blot analysis for changes in protein concentration and activation. RESULTS: Roxarsone was found to exhibit a higher angiogenic index than As(III) at lower concentrations. Increased endothelial nitric oxide synthase (eNOS) activity was observed for roxarsone but not for As(III)-induced angiogenesis. However, As(III) caused more rapid and pronounced phosphorylation of eNOS. Quantitative PCR array on select genes revealed that the two compounds have different and often opposite effects on angiogenic gene expression. CONCLUSIONS: The results demonstrate that roxarsone and As(III) promote angiogenic phenotype in human endothelial cells through distinctly different signaling mechanisms.